Consequences at adulthood of transient inactivation of the parahippocampal and prefrontal regions during early development: new insights from a disconnection animal model for schizophrenia - Meyer, Francisca; Louilot, Alain (Frontiers in Behavioral Neuroscience, 2014)
The psychic disintegration characteristic of schizophrenia is thought to result from a defective connectivity, of neurodevelopmental origin, between several integrative brain regions. The parahippocampal region and the prefrontal cortex are described as the main regions affected in schizophrenia. Interestingly, latent inhibition (LI) has been found to be reduced in patients with schizophrenia, and the existence of a dopaminergic dysfunction is also generally well accepted in this disorder. In the present review, we have integrated behavioral and neurochemical data obtained in a LI protocol involving adult rats subjected to neonatal functional inactivation of the entorhinal cortex, the ventral subiculum or the prefrontal cortex. The data discussed suggest a subtle and transient functional blockade during early development of the aforementioned brain regions is sufficient to induce schizophrenia-related behavioral and dopaminergic abnormalities in adulthood. In summary, these results support the view that our conceptual and methodological approach, based on functional disconnections, is valid for modeling some aspects of the pathophysiology of schizophrenia from a neurodevelopmental perspective.